Analysis of biodiversity in the Pamotan Mudal spring area, Rembang Regency. Issue 1 (November 2021) - Rachmawati, S; Matin, H H A; Suhardono, S; Setyono, P; Kusumaningrum, L; Rinawati, S; Wijaya, D S
Abstract: The community's need for clean water is increasing along with the increase in population. In fulfilling clean water, most will use surface water and underground water. Mudal spring is one of the springs located in Pamotan District, Rembang Regency, and has 80 liters/second discharge. The community uses the uses of springs to meet their needs, such as drinking water and irrigation. This study aims to determine the diversity of fauna and flora of the Mudal spring area and identify the use and conservation efforts of the springs by the community in Pamotan District, Rembang Regency. This research uses descriptive quantitative research. Data were analyzed using the Shannon-Wienner Diversity Index formula. There are ten types of fauna in the Mudal spring area with a diversity index H'=1.82 which is included in the medium category. As for flora, 17 species were found with a diversity index H'=1.83 which was included in the medium category. The conservation and utilization efforts carried out by the surrounding community for the Mudal spring are reasonable enough so that it is necessary to improve the concept of sustainable and environmentally sound management so that it remains by following with its function.